Hermetic Seed Storage to Enhance Seed Longevity in Acid Lime (Citrus aurantifolia Swingle) - PALLAVI HM; DHANANJAY B; BAPURAYAGOUDA PATIL; ANAND GN; SOWMYA KJ (Seed Research, 2026)
Storage capability of acid lime seeds are under question due to its intermediate to recalcitrant nature. Seed desiccation tolerance limits plays major role in storage of seeds with better viability for propagation in citrus. An experiment was conducted to explore the effect of desiccation limits on germination and influence of storage conditions on seed viability. Fresh seeds of kagzi acid lime were collected and studied for its germination and storability. Results showed that as the moisture content was reduced from 50.06% to 11.97%, the mean germination percentage was also reduced from 85.0% to 39.0% indicating sensitivity to desiccation tolerance and exhibited recalcitrant to intermediate storage behavior. The results of storage experiments showed that seeds packed in aluminum foil and stored at 100C could retain high germination (62%) and seedling growth parameters up to 3 weeks of storage.